Implementing laboratory computerized systems in pharmaceutical industry - Peklaj, Kristian (Ventil (Ljubljana), 2025)
The implementation of computerized systems in pharmaceutical industry must meet the compliance with regulatory requirements, assure high level of data integrity (DI) and product quality. This study reviews European legislation, the European and U.S. pharmacopoeias, and global guidelines, such as GAMP 5 and ALCOA++, to identify the necessary standards and best practices. Key directives of European and U.S legalisation emphasize the importance of system validation, quality risk management and secure data handling. The study highlights validation processes categorized by system complexity according to GAMP 5. Additionally, guidelines like ALCOA++ provide a robust framework for achieving DI throughout the data lifecycle. By adhering to these requirements, pharmaceutical manufacturers can ensure regulatory compliance, maintain high-quality standards and safeguard patient safety.
Keywords: compliance; computerized systems; data integrity; GAMP 5; pharmacy; regulations; validation